Tree diameters and planting distance as the most important factors for the liberation of tree competitors in sylvicultural systems of TPTJ - Pamoengkas, Prijanto; Gandaseca, Seca; Hardiansyah, Gusti; Priyanto,; Jamaludin, Muhamad Rizky (Science Publishing Group, 2014)
Maintenance of forest plants intensively under the selective cutting and line planting system (TPTJ) will accelerate the growth of plant species. Widening the line planting improves the penetrating light, thus increasing growth rate of the plants. The purpose of this study was to determine the relationship between stem diameter and distance of competitor tree to forest plant, as well as stem diameter and canopy diameter as a basis for the liberation of competitor trees on the TPTJ system. Regression analysis showed that the competitor trees diameter and distance can be used as one technique of vertical liberation with equation correlation for both variables is X=3.567−0797dbh+0.121dbh2−0.004dbh3. The approach of liberation using correlation between stem diameter and canopy diameter can not be used as a vertical liberation technique with equation correlation between the two variables is Cda=2.535−0.031dbh + 0.050dbh2−0.002dbh3. The study revealed that saplings with diameter (dbh) 5−9cm located at 1−2.5 m of subplots must be slashed down. For sapling with diameter (dbh) ≥10 cm dbh located at 3−5 m of the center of planting line must be girdled.